2014
DOI: 10.1080/01446193.2014.933854
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with construction cost overruns using data mining

Abstract: One of the main aims of any construction client is to procure a project within the limits of a predefined budget. However, most construction projects routinely to overrun their cost estimates. Existing theories on construction cost overrun suggest a number of causes ranging from technical difficulties, optimism bias, managerial incompetence and strategic misrepresentation. However, much of the budgetary decision making process in the early stages of a project is carried out in an environment of high uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 43 publications
1
30
0
2
Order By: Relevance
“…Our study offers four broad theoretical implications related to ROR. First, prior to our study, there have been few attempts to formulate perspectives that allow the simultaneous study of multiple causes of an inadequate development process [19], [28], [62]. In addition, few studies have shown that decision-makers apply the logic of real options in project settings [4], [16], [43].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Our study offers four broad theoretical implications related to ROR. First, prior to our study, there have been few attempts to formulate perspectives that allow the simultaneous study of multiple causes of an inadequate development process [19], [28], [62]. In addition, few studies have shown that decision-makers apply the logic of real options in project settings [4], [16], [43].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Ahiaga-Dagbui ve Smith çalışmalarında [24], bir projenin ilk aşamalarında bütçesel karar vermede az bilgi ile doğru tahmini gerçekleştirmek için yapay sinir ağlarında parametrik olmayan topluluk modellemesi kullanarak 1600 tamamlanmış projeden aldığı veri ile nihai proje maliyet tahmin modelleri geliştirmişlerdir. Çalışma sonucunda, 100 doğrulama öngörüsünün %92'sinin projenin fiili nihai maliyetinin ±%10'u dahilinde olduğu bulunurken, %77'sinin fiili nihai maliyetin ±%5'i dahilinde gerçekleştiği tespit edilmiştir.…”
Section: Veriunclassified
“…These models are based on regression analysis and case based reasoning. Ahiaga-Dagbui and Smith [22] made a case for using data mining in modern construction management as a key business tool to help transform information embedded in the construction data into decision support systems that can complement traditional estimation methods for more reliable final cost forecasting. Using a combination of non-parametric bootstrapping and ensemble modelling in artificial neural networks, cost models were developed to estimate the final construction cost of water infrastructure projects.…”
Section: Introductionmentioning
confidence: 99%